Indirect CRISPR screening with photoconversion revealed key factors of drug resistance with cell–cell interactions - Keisuke Sugita; Iichiroh Onishi; Ran Nakayama; Sachiko Ishibashi; Masumi Ikeda; Miori Inoue; Rina Narita; Shiori Oshima; Kaho Shimizu; Shinichiro Saito; Shingo Sato; Branden S. Moriarity; et al. (Communications Biology, 2023)
Abstract Comprehensive screenings to clarify indirect cell–cell interactions, such as those in the tumor microenvironment, especially comprehensive assessments of supporting cells’ effects, are challenging. Therefore, in this study, indirect CRISPR screening for drug resistance with cell–cell interactions was invented. The photoconvertible fluorescent protein Dendra2 was inducted to supporting cells and explored the drug resistance responsible factors of supporting cells with CRISPR screenings. Random mutated supporting cells co-cultured with leukemic cells induced drug resistance with cell–cell interactions. Supporting cells responsible for drug resistance were isolated with green-to-red photoconversion, and 39 candidate genes were identified. Knocking out C9orf89, MAGI2, MLPH, or RHBDD2 in supporting cells reduced the ratio of apoptosis of cancer cells. In addition, the low expression of RHBDD2 in supporting cells, specifically fibroblasts, of clinical pancreatic cancer showed a shortened prognosis, and a negative correlation with CXCL12 was observed. Indirect CRISPR screening was established to isolate the responsible elements of cell–cell interactions. This screening method could reveal unknown mechanisms in all kinds of cell–cell interactions by revealing live phenotype-inducible cells, and it could be a platform for discovering new targets of drugs for conventional chemotherapies.